Formation of Money Supply, Taking into Account the Role of Virtual Assets - Serhii Zashchypas (Облік і фінанси, 2025)
The introduction of such tools as Initial Coin Offerings (ICO), Decentralized Finance (DeFi) platforms and smart contracts creates new opportunities for raising capital. However, this segment of the digital economy requires a comprehensive approach to understanding the principles of its functioning, considering the interests of all stakeholders and potential systemic consequences. The article aims to study the impact of virtual assets on the monetary sphere, particularly on the volume of money supply, the effectiveness of monetary policy implementation and the financial system's stability. The study's results indicate that the evolution of virtual assets requires a revision of traditional theories of money supply. None of the classical theories – neither exogenous nor endogenous – can fully capture the specifics of the emission of virtual assets, in particular, due to its decentralized and technologically autonomous nature. Based on recent empirical research and macroeconomic trends, it has been shown that virtual assets and central bank digital currency (CBDC) can directly or indirectly change the dynamics of monetary aggregates, influencing the velocity of money, the structure of deposits and the transmission of monetary impulses. The analyzed results of previous studies indicate the ambiguous but increasing role of virtual assets in transforming the modern financial system. In addition, virtual assets can be a factor affecting the level of monetization of the economy by replacing traditional banking instruments. Thus, virtual assets can act not only as a new financial instrument but also as a factor influencing macroeconomic stability. The results of this study can be used to form an updated architecture of monetary policy.